PENGARUH IKLIM ORGANISASI DAN KEPUASAN KERJA TERHADAP TURNOVER INTENTIONS DAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING PADA PT. PANCA SURYA AGRINDO (PSA) KABUPATEN ROKAN HULU - Ratna Dewi; Marnis '; Restu ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The research was conducted at PT. Panca Surya Agrindo Kabupaten Rokan Hulu. With the aim to identify and analyze Influence of climate organization and job satisfaction to turnover intentions and organizational commitment as an intervening variable at PT. Panca Surya Agrindo Kabupaten Rokan Hulu. Where in this study population was all employees at PT. Panca Surya Agrindo Kabupaten Rokan Hulu. totaling 148 people . The sample used in this study were 108 employees and data processing using path analysis with SPSS. Based on the test results if the data using path analysis can be drawn some conclusions, namely: Organizational climate effect on turnover Intention employees at PT. Panca Surya Agrindo Rokan Hulu, job satisfaction influence on turnover Intention employees at PT. Panca Surya Agrindo Rokan Hulu, employee commitment effect on turnover Intention employees at PT. Panca Surya Agrindo Rokan Hulu, organizational climate affect the commitment of employees at PT. Panca Surya Agrindo Rokan Hulu, job satisfaction affect the commitment of employees at PT. Panca Surya Agrindo Rokan Hulu, Climate influential organizations through employees commitment to turnover Intention in PT. Panca Surya Agrindo Rokan Hulu, influence job satisfaction through employee commitment to the turnover Intention in PT. Panca Surya Agrindo Rokan Hulu, So it is expected to the company to be able to impose sanctions on employees who are lazy bekrja, for example by reducing the compensation, both financial and non-financial. So that it can improve work effectiveness and employee performance.Keyword: Organizations Climate, commitment, And Turnover Intention.